1987
DOI: 10.1200/jco.1987.5.6.851
|View full text |Cite
|
Sign up to set email alerts
|

Combination chemotherapy using adriamycin, DTIC, cyclophosphamide, and actinomycin D for advanced soft tissue sarcomas: a randomized comparative trial. A phase III, Southwest Oncology Group Study (7613).

Abstract: The term soft tissue sarcoma refers to a large variety of malignant tumors arising in extraskeletal connective tissues that connect, support, and surround discrete anatomic structures. All visceral organs also contain a connective stroma that can undergo malignant transformation. Because of the histological similarities of this group of tumors and their relative rarity, treatment prescriptions for patients that have disseminated disease are most often uniform. In this study, we asked the question whether addin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
24
0
1

Year Published

1990
1990
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(30 citation statements)
references
References 8 publications
5
24
0
1
Order By: Relevance
“…Because of variability in patient populations, direct comparisons between studies have limited value. However, a response rate of 27% is in keeping with many other studies of intermittent high dose ADR (Bramwell et al, 1983;Mouridsen et al, 1987;Santoro et al, 1990), and is similar to the respose rate for ADIC (30%) in this second ECOG trial (Bordon et al, 1987) and for ADIC (33%) in the SWOG trial (Baker et al, 1987). Benjamin's editorial (1987) suggested that 'IFOS intensification' might produce better results.…”
supporting
confidence: 62%
See 1 more Smart Citation
“…Because of variability in patient populations, direct comparisons between studies have limited value. However, a response rate of 27% is in keeping with many other studies of intermittent high dose ADR (Bramwell et al, 1983;Mouridsen et al, 1987;Santoro et al, 1990), and is similar to the respose rate for ADIC (30%) in this second ECOG trial (Bordon et al, 1987) and for ADIC (33%) in the SWOG trial (Baker et al, 1987). Benjamin's editorial (1987) suggested that 'IFOS intensification' might produce better results.…”
supporting
confidence: 62%
“…Although the response rate for single agent ADR was higher than the 19% achieved with the second combination regimen (VCR + ADR + CYCLO) used in this study, the difference was not significant. A later trial by SWOG, randomising 335 patients (Baker et al, 1987), showed that adding CYCLO or DACT to the ADIC regimen did not significantly improve response rates, which were respectively 33% (ADIC), 34% (CYCLO/ADIC) and 24% (DACT/ADIC).…”
mentioning
confidence: 99%
“…Finally, many investigators are of the opinion that some histological types of ASTS respond poorly to chemotherapy, in particular leiomyosarcomas of gastrointestinal origin. However, convincing evidence for this is difficult to find in the literature [8,10,12]. Dose-response relationships Is there a strong proven dose-response relationship in ASTS, so that the effect of chemotherapy can be increased by simply increasing the dose?…”
Section: Prognostic Factors For Chemotherapy Responsementioning
confidence: 99%
“…There are indications that some cytostatic agents may have higher activity for certain histological types, including ifosfamide and doxorubicin for synovial sarcomas [4,10], and OTIC-containing combinations for leiomyosarcomas [II,12].…”
Section: Activity Of Individual Chemotherapeutic Agentsmentioning
confidence: 99%
“…Yap et al treated 125 ae ORIGINAL ARTICLE ae advanced STS patients with a combination of doxorubicin, dacarbazine, cyclophosphamide, and vincristine, the socalled 'CYVADIC regimen', with a reported RR of 50% (8). In 1976 Á/1979, in a randomized study by the Southwest Oncology Group (SWOG) comprising 112 patients, three treatment combinations were compared, i.e., doxorubicin'/ dacarbazine vs. doxorubicin'/dacarbazine'/cyclophosphamide vs. doxorubicin'/dacarbazine'/actinomycin D, but no statistically significant differences in RR were found (33%, 34%, and 24%) (9). In a randomized study comprising 663 patients with advanced STS conducted by the European Organization for Research and Treatment of Cancer (EORTC), it was concluded that single-agent doxorubicin should be the standard treatment.…”
mentioning
confidence: 99%